2019
DOI: 10.1016/j.cgh.2019.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Deficits in Patients With Newly Diagnosed Celiac Disease Are Frequent and Linked With Autoimmunity to Transglutaminase 6

Abstract: BACKGROUND & AIMS:Celiac disease is an autoimmune disorder induced by ingestion of gluten that affects 1% of the population and is characterized by gastrointestinal symptoms, weight loss, and anemia. We evaluated the presence of neurologic deficits and investigated whether the presence of antibodies to Transglutaminase 6 (TG6) increases the risk of neurologic defects in patients with a new diagnosis of celiac disease. METHODS:We performed a prospective cohort study at a secondary-care gastroenterology center o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 37 publications
(29 reference statements)
4
56
0
6
Order By: Relevance
“…Imaging studies of CD have been integral in characterising the brain tissue injury found in CD. Lowered brain volume in the cerebellum (whole cerebellar grey matter) and thalamus has been found in patients with TG6 positivity [24], while white matter changes affecting the tract connecting those regions (spinothalamic) in addition to the corpus callosum have been reported as a more general finding [14]. These brain locations are known to hold associations with the cognitive functions found to be impaired in the current study.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Imaging studies of CD have been integral in characterising the brain tissue injury found in CD. Lowered brain volume in the cerebellum (whole cerebellar grey matter) and thalamus has been found in patients with TG6 positivity [24], while white matter changes affecting the tract connecting those regions (spinothalamic) in addition to the corpus callosum have been reported as a more general finding [14]. These brain locations are known to hold associations with the cognitive functions found to be impaired in the current study.…”
Section: Discussionmentioning
confidence: 43%
“…Circulating antibodies against gluten products are thought to be the primary cause of underlying brain pathology in gluten-related conditions. Transglutaminase 6 (TG6), an antibody common in gluten ataxia and also present in CD patients at a rate of approximately 40% [24], is expressed in a number of brain regions and particularly the cerebellum [25]. This may explain the characteristic patchy loss of cerebellar Purkinje cells observed in gluten ataxia [7].…”
Section: Discussionmentioning
confidence: 99%
“…The brain has been shown to be affected in a number of gluten-related disorders, from blunt neurological conditions like gluten ataxia [25] to "classical" CD [16,17,26,27]. In the current study neurological symptoms during typical gluten reactions of "classic" NCGS patients were reported at high rates, including headaches and brain fog each in approximately half of the group, as well as feeling off-balance in a third of subjects and sensory symptoms in a fifth.…”
Section: Discussionmentioning
confidence: 55%
“…White matter lesions are a non-specific brain pathology known to occur during normal aging [29]. However, they appear with greater size and frequency in a number of conditions such as vascular dementia [30] and multiple sclerosis [31], and have also been reported as an outcome in CD [16] (potentially linking with the increased risk of vascular dementia which CD is known to carry [32]). Similarly, low NAA/Cr is also known to be present in CD [17] and other neurological gluten conditions such as gluten ataxia [33].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation